Swot Analysis Utilization In Designing Performance Development Strategy for Micro, Small & Medium Enterprises in Malang Area Coordinator - Hermawati, Adya (International Journal of Psychosocial Rehabilitation, 2020)
The Department of Cooperative and Micro, Small & Medium Enterprises (MSMEs) in Malang Area Coordinator has given its endeavor to develop MSMEs to become the economic power with strong commitment to improve people welfare. Research objective is to utilize SWOT in designing performance development strategy for MSMEs in Malang Area Coordinator. Primary data were used and collected with questionnaire distributed to respondents at 120 MSMEs in 6 regencies or cities in Malang Area Coordinator. Analysis instrument of this research is SWOT, and the reason of its selection is that it allows researcher to identify and understand strength, weakness, opportunity and threat around the development of MSMEs in Malang Area Coordinator. Internal and external factors of MSMEs in Malang Area Coordinator, either as a whole or per location, are evaluated. Result of this evaluation shows that MSMEs are in a good position, which is in Quadrant I. Therefore, the expected strategy is Strength-Opportunity (SO).